Boswell's London journal, 1762-1763 - Boswell, James, 1740-1795 (The Yale Editions of the Private Papers of James Boswell : YEPPJB, 2004)
In 1762 James Boswell, then twenty-two years old, left Edinburgh for London. The famous Journal he kept during the next nine months is an intimate account of his encounters with the high-life and the low-life in London. Frank and confessional as a personal portrait of the young Boswell, the Journal is also revealing as a vivid portrayal of life in eighteenth-century London. This new edition includes a Foreword by Peter Ackroyd, which discusses Boswell's life and achievement.